Methods And Physico-Chemical Fundamentals Of Toxic Waste Recycling In Local Conditions (Conference Zone, 2022)
These days of advanced science, mankind's need for vehicles is growing. In turn, the car industry is developing year by year in the world and in our country. According to statistics, in 2017, there were 83 cars per 1,000 people in Uzbekistan. In neighboring countries, the figure is much higher: for example, in Kazakhstan - 250 cars per 1,000 people, in Russia - 334 cars per 1,000 people. In Uzbekistan, it is planned to increase this figure to 237 cars per 1,000 people by 2025. Along with the increase in the number of vehicles among the population, the number of tires that are disposed as waste after the end of their service life is also increasing.Waste tires, which were already used, are currently used for a variety of purposes among countries around the world.